Perfiles académicos de los estudiantes de pregrado en Ingeniería Industrial (2020)
The objective of this project is to propose a classification of the current academic profiles of undergraduate students of industrial engineering at the Universidad de los Andes, in order to strengthen the process of curricular reform that is being carried out. For this, a qualitative research was carried out with a participatory methodology, a tool was implemented through two different computational methods (classical unsupervised methods and natural language processing), the viability of the profiles, proposed by the industrial engineering department, was established, and a new profile and themes to be included within the academic curriculum were proposed.